Peptidomic analysis of follicular fluid in patients with polycystic ovarian syndrome - Sun, Ningyu; Chen, Yuanyuan; Lu, Lu; Yan, Hua; Zhou, Jing; Li, Kai; Zhang, Wuwen; Yuan, Lihua; Heng, Boon Chin; Zeng, Weiwei; Shi, Yin; Tong, Guoqing; et al. (Frontiers in Cell and Developmental Biology, 2023)
The aim of this study was to analyze and compare the differential expression of peptides within the follicular fluid of polycystic ovary syndrome (PCOS) patients versus normal women by using peptidomics techniques. The underlying mechanisms involved in PCOS pathogenesis will be explored, together with screening and identification of potential functional peptides via bioinformatics analysisA total of 12 patients who underwent in vitro fertilization and embryo transfer (IVF-ET) at the Reproductive Medicine Center of Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine from September 1, 2022 to November 1, 2022 were included in this study.